Microwave-Promoted Synthesis of Sulfonated Metallophthalocyanines and Aggregation in Different Solvents - Zhenhua Cheng; Na Cui; Shengjuan Jiang; Hongxiao Zhang; Lijun Zhu; Daohong Xia (Advances in Materials Science and Engineering)
Five metallosulfophthalocyanines (Fe, Ni, Zn, Co, and Cu) compounds were synthesized by microwave irradiation. Compared to the conventional method of synthesis in terms of reaction time and yields, the microwave-promoted synthesis is preferred with high product yield and short reaction time. All synthesized products were characterized with MALDI-TOF mass spectrum, Fourier transform infrared spectroscopy (FT-IR), ultraviolet-visible spectroscopy (UV-Vis), and X-ray diffraction (XRD). Aggregation behavior of the five metallosulfophthalocyanines (MSPc) in different solvents was studied by UV-Vis spectroscopy separately in N,N-dimethyl formamide (DMF) and NaOH aqueous solution (5%wt). A redshift of maximum absorption wavelength and deviations from Lambert-Beer law with increasing the concentration were observed. The dimerization equilibrium constants (K) of the five MSPc were determined, respectively.